The Effect Of Assemblr Edu Learning Media On Social Science Learning Outcomes - Sari, Delvi Manda; Afriandi, Putra; Simanungkalit, Erlinda; Mailani, Elvi; Manurung , Imelda Free Unita (Yana Research, 2024)
This research aims to determine the influence of the Assembir Edu learning media on the learning outcomes of class IV science class Mis Nurus Salam Deli Tua. This research method is a quantitative research method using a gore pernental (quasi-experimental) research design, in the form of a non-equivalent conventional group design. The sample for this research is all class IV Mis Nurus Salam Deli Tua, totaling 53 students with the experimental class class IV A with a total of 26 students and class IV B as a control class with a total of 27 students. The data collection method in this research was a multiple choice session consisting of 20 data analysis tests which were used statistically through a single test for two independent samples (dependent samples, the results of the study showed that the Zembo El learning media has an effect on the science and science learning outcomes for class IV, Mis Nurus Salam Deli Tua. Descriptively, the average posture score for the control class is 57,04, which is smaller and the average market value for the experimental class is 73,85. Furthermore, the unit hypothesis result is 5,10 > 2,01. with a significant level of 5% or 005 which means Ho is processed and Ha is received. Thus, statistically it can be stated that Amit's learning media has an equally significant effect on increasing the level of science learning skills for class IV science students. Mis Nurus Salam Deli Tua.